Risk factors for specific subtypes of ischaemic stroke - Schulz, U; Schulz, Ursula (2004)
﻿ Ischaemic stroke is a complex disorder with many different aetiologies, but previous studies of stroke often did not differentiate aetiological subtypes of ischaemic stroke. However, different stroke subtypes may have different risk factors, and to target preventive treatments more effectively, we need to understand these associations. I studied the association of established vascular risk factors with different aetiological stroke subtypes in population-based cohorts of stroke patients. I studied Diffusion Weighted Magnetic Resonance Imaging (DWI) in patients with subacute minor stroke and TIA to determine whether DWI may be a useful addition to the management of such patients, and whether it may be a useful tool in future epidemiological studies of stroke. To determine whether carotid anatomy may be a risk factor for large vessel atheroma I studied angiographical data from the European Carotid Surgery Trial. My main findings are that the prevalence of risk factors differs between stroke subtypes. It also differs between hospitalised and non-hospitalised patients, highlighting that risk factor studies should be performed in population-based cohorts. Analysis of family history data suggests that future genetic studies may best be targeted at non-cardioembolic stroke and at younger patients, and that genetic studies of hypertension may help to unravel some of the genetic factors contributing to stroke risk. DWI is sensitive in subacute minor stroke, and inter- and intra-observer reproducibility are high. DWI frequently adds useful information and may influence patient management. More widespread use of DWI in patients with subacute stroke and TIA should be considered, and DWI may also be a useful tool in future epidemiological studies of stroke. Carotid anatomy varies considerably between individuals, is very asymmetrical within individuals, and it differs between men and women. These findings may partly explain differences in plaque development between individuals, asymmetrical plaque formation within individuals, and sex differences in the distribution of carotid plaque and in the prevalence of carotid atheroma in the general population. Carotid anatomy may be a risk factor for local plaque development. Although not amenable to treatment, knowing which anatomical configuration is associated with atheroma formation could help to identify high-risk individuals in whom other risk factors should be treated aggressively.